Transmission Electron Microscopy and Diffractometry of Materials - Fultz, Brent; Howe, James; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
This book explains concepts of transmission electron microscopy (TEM) and x-ray diffractometry (XRD) that are important for the characterization of materials. The third edition has been updated to cover important technical developments, including the remarkable recent improvement in resolution of the TEM. This edition is not substantially longer than the second, but all chapters have been updated and revised for clarity. A new chapter on high resolution STEM methods has been added. The book explains the fundamentals of how waves and wavefunctions interact with atoms in solids, and the similarities and differences of using x-rays, electrons, or neutrons for diffraction measurements. Diffraction effects of crystalline order, defects, and disorder in materials are explained in detail. Both practical and theoretical issues are covered. The book can be used in an introductory-level or advanced-level course, since sections are identified by difficulty. Each chapter includes a set of problems to illustrate principles, and the extensive Appendix includes laboratory exercises. ``I can warmly recommend this book, which is attractively priced, as an excellent addition for any materials scientist or physicist who wants a good overview of current diffraction and imaging techniques.'' John Hutchison in Journal of Microscopy ``I can recommend it as a valuable resource for anyone involved in a higher-level course on materials characterization.'' Ray Egerton in Micron ``A wonderful book. A rare combination of depth, practical advice, and problems for every aspect of modern XRD, TEM, and EELS. No materials lab should be without it now that TEM/STEM has become such a crucial tool for nanoscience.'' John C. H. Spence, Arizona State University ``I give a lecture course here on Advanced Electron Microscopy and will certainly be recommending your book for my course. It is a superb book.’’ Colin Humphreys, Cambridge University ``This text offers the most complete pedagogical treatment of scattering theory available in a single source for graduate instruction in contemporary materials characterization. Its integration of photons and electrons, beam lines and electron microscopes, theory and practice, assists students with diverse scientific and technical backgrounds to understand the essence of diffraction, spectrometry and imaging. Highly recommended.’’ Ronald Gronsky, University of California, Berkeley.
Diffraction and the X-Ray Powder Diffractometer -- The TEM and its Optics -- Scattering -- Inelastic Electron Scattering and Spectroscopy -- Diffraction from Crystals -- Electron Diffraction and Crystallography -- Diffraction Contrast in TEM Images -- Diffraction Lineshapes -- Patterson Functions and Diffuse Scattering -- High-Resolution TEM Imaging -- High-Resolution STEM Imaging -- Dynamical Theory.
Keywords: Materials science; Materials—Surfaces.; Thin films; Crystallography; Solid state physics; Spectroscopy; Microscopy; Engineering; Characterization and Evaluation of Materials; Surfaces and Interfaces, Thin Films; Crystallography and Scattering Methods; Solid State Physics; Spectroscopy and Microscopy; Engineering, general